Radix Codonopsis: a review of anticancer pharmacological activities - Liu, Cai-Yue; Li, Zheng; Cheng, Fan-E.; Nan, Yi; Li, Wei-Qiang (Frontiers in Pharmacology, 2025)
Radix Codonopsis (Dangshen), derived from the dried root of plants in the Campanulaceae family, is a widely used Chinese herbal medicine. It is renowned for its pharmacological effects, including tonifying the middle qi, invigorating the spleen, benefiting the lungs, enhancing immunity, and nourishing the blood. Codonopsis extract is frequently incorporated into health products such as tablets and capsules, making it accessible for daily health maintenance. Additionally, it is commonly used in dietary applications like soups, teas, and porridges to nourish qi, enrich blood, and promote overall vitality. In recent years, increasing attention has been given to the anti-cancer potential of Radix Codonopsis. Studies have identified key active components such as luteolin, stigmasterol, polyacetylenes, lobetyolin, and glycitein, which exhibit anti-tumor properties through mechanisms like inhibiting cancer cell growth and proliferation, suppressing epithelial-mesenchymal transition (EMT), and inducing apoptosis. This review highlights the research progress on Radix Codonopsis, including its active constituents, anti-cancer mechanisms, and its role in the convergence of medicine and food in modern life. By doing so, it aims to provide valuable insights and references for future scientific studies and clinical applications of Radix Codonopsis.